Investigating The Load Carrying Capacities of Lightweight Foamed Concrete Strengthen with Fiber Mesh - Othuman, Azree; Mat Serudin, Anisah; Abdul Ghani, Abdul Naser (International Journal of Integrated Engineering, 2022)
Lightweight foamed concrete (LFC) is well known as a low-density concrete with a wide range of applications. However, since its weight is almost half that of conventional concrete, its strength can also be expected to be lower than that of normal concrete. Thus, short fibres (synthetic and natural fibres) were used by previous researchers to improve the performance of LFC. Even though there were improvements in its mechanical properties, yet these had a negative impact on its durability in the long term due to the deterioration of the fibres. Recently, the use of fibre-glass mesh as a reinforcing element has gained considerable attention. Thus, the aim of this research was to perform an experimental investigation to establish the mechanical performance of carbon fibre-glass mesh (CFGM) reinforced LFC. In this research, LFC specimens were designed with densities of 650 kg/m3, 1150 kg/m3 and 1600 kg/m3 with a constant cement-to-sand ratio of 1:1.5, and cement-to-water ratio of 0.45. The CFGM selected for this research was woven fiberglass mesh with a weight per area of 145 g/m2. The number of layer(s) for the observed confinement was detailed down to its effect on the performance of the LFC. The mechanical properties of the LFC were examined through compressive, flexural, and splitting tensile tests. Overall, the reinforcement with CFGM improved the mechanical performance of the LFC. A confinement with 3 layers of CFGM showed significant results, where enhancements of 153% (650 kg/m3), 97% (1150kg/m3), and 102% (1650 kg/m3) were obtained for the compressive strength; 372% (650 kg/m3), 258% (1150 kg/m3), and 332% (1650 kg/m3) for the flexural strength; and 507% (650 kg/m3), 343% (1150 kg/m3), and 332% (1650 kg/m3) for the tensile strength, respectively, compared to the control LFC.